2021
DOI: 10.3390/antiox10111809
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Browning Degree and Reducibility of Polyphenols during Autoxidation and Enzymatic Oxidation

Abstract: In the present study, the browning degree and reducing power of browning products of catechin (CT), epicatechin (EC), caffeic acid (CA), and chlorogenic acid (CGA) in autoxidation and enzymatic oxidation were investigated. Influencing factors were considered, such as pH, substrate species and composition, and eugenol. Results show that polyphenols’ autoxidation was intensified in an alkaline environment, but the reducing power was not improved. Products of enzymatic oxidation at a neutral pH have higher reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…The innate antioxidant property of the unmodified CS film is generally ascribed to chitosan’s hydroxyl groups and amino groups [ 42 ]. The functionalization of CS with several phenolic compounds in their native or oxidized form has been demonstrated to lead to an enhancement in its reducing power [ 84 , 85 ]. This enhancement is attributed to the hydroxyl groups of the phenolic compounds and their oxidation products that can donate a hydrogen atom to stabilize the ABTS radical [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…The innate antioxidant property of the unmodified CS film is generally ascribed to chitosan’s hydroxyl groups and amino groups [ 42 ]. The functionalization of CS with several phenolic compounds in their native or oxidized form has been demonstrated to lead to an enhancement in its reducing power [ 84 , 85 ]. This enhancement is attributed to the hydroxyl groups of the phenolic compounds and their oxidation products that can donate a hydrogen atom to stabilize the ABTS radical [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenol autoxidation refers to the reaction of polyphenols with oxygen to produce o ‐quinones and related products under the catalysis of metal ions. Based on a number of experimental studies, the current mechanism proposes that under the catalysis of iron(II), oxygen reacts with polyphenols, especially o ‐diphenols, to produce a semiquinone, and then an o ‐quinone (Zhou, Tian, et al., 2021; Zhou, Iqual, et al., 2021). Maegawa et al.…”
Section: O‐quinone Generation Mechanismsmentioning
confidence: 99%
“…Zhou et al. (2021) reported that enzymatic oxidation is faster than nonenzymatic and triggers more complicated oxidative reactions. Hence, PPO makes great contributions to o ‐quinone production and subsequent complex reactions.…”
Section: Factors Influencing O‐quinone Formation and Reactivitymentioning
confidence: 99%
See 2 more Smart Citations